Malware detection in blockchain using CNN - Alam, Afreen; Islam, Humaira; Wamim, Sadman Arif; Ahmed, Md. Tanjim; Siddiqi, Hasnat (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.